Analysis of flow and temperature distribution in a full scale utility boiler using CFD - Hasini H.; Yusoff Mohd.Z.; Shuaib N.H.; Boosroh Mohd.H.; Haniff M.A. (2023)
There are currently numerous studies on utility boilers using various in-house and commercial CFD codes. Most of the existing simulations are aimed at the flow and combustion properties inside the furnace and therefore, it usually terminates at furnace exit just downstream the re-heater section before the crossover path. On top of that, the majority of these works were based on coal-fired boiler furnace, which has completely different combustion characteristics as compared to natural gas fired boiler. This paper describes an investigation of the prediction of combustion characteristics and flow pattern in a gas-fired boiler. The emphasis is given towards the analysis of flow pattern and its distribution inside the furnace in a steady-state manner. In this investigation, the flow path is extended so that the rear pass, which normally been ignored is included in the calculation domain. Commercial CFD code, CFD ACE+ was used as a tool to carry out the analysis. 2009 IEEE.